Concurrent Ventral Hernia Repair Is Effective in Patients Undergoing Abdominally Based Microsurgical Breast Reconstruction - Kraft, Casey T.; Chao, Albert H. (Journal of Reconstructive Microsurgery, 2020)
Background The abdomen remains the most preferable donor site for autologous breast reconstruction. Many patients in this population will have had prior abdominal surgery, which is the chief risk factor for having a ventral hernia. While prior studies have examined the impact of prior abdominal surgery on breast reconstruction, limited data exist on the management of patients with a preexisting ventral hernia. The objective of this study was to investigate outcomes of performing ventral hernia repair concurrent with abdominally based microsurgical breast reconstruction.Methods A 5-year retrospective review of patients undergoing abdominally based microsurgical breast reconstruction was performed. The experimental group consisted of patients with a preexisting ventral hernia that was repaired at the time of breast reconstruction, and was compared with a historical cohort of patients without preexisting hernias.Results There were a total of 18 and 225 patients in the experimental and control groups, respectively. There was a higher incidence of prior abdominal surgery in the experimental group (p = 0.0008), but no other differences. Mean follow-up was 20.5 ± 5.2 months. There were no instances of recurrent hernia or flap loss in the experimental group. No significant differences were observed between the experimental and control groups in the incidence of donor-site complications (27.8 vs. 20.9%, respectively; p = 0.55), recipient site complications (27.8 vs. 24.0%, respectively; p = 0.78), operative time (623 ± 114 vs. 598 ± 100 minutes, respectively; p = 0.80), or length of stay (3.4 ± 0.5 vs. 3.1 ± 0.4 days, respectively; p = 0.98).Conclusion Concurrent ventral hernia repair at the time of abdominally based microsurgical breast reconstruction appears to be safe and effective. Larger studies are needed to further define this relationship.
Keywords: breast reconstruction; hernia; hernia repair